The effects of obstructive sleep apnea syndrome due to adenotonsillar hypertrophy on the cardiovascular system in children - Tatlıpınar, Arzu; Duman, Dursun; Uslu, Celil; Egeli, Erol (The Turkish Journal of Pediatrics, 2011)
Obstructive sleep apnea syndrome (OSAS) due to adenotonsillar hypertrophy (ATH) is a common and important problem in children. OSAS can lead to significant cardiopulmonary complications, poor growth and problems with learning and behavior. Many studies in the literature show that OSAS due to ATH causes pulmonary hypertension, ventricular hypertrophy and systemic hypertension in the pediatric population. In this review, we discuss the effects of ATH on cardiac function. It is well known that as a child grows, the nasopharyngeal passage becomes enlarged, helping to improve OSAS. Based on this, we discuss the possible positive effect of this age-related improvement on the obstruction of cardiovascular disturbances. Finally, the possible relationship between the duration of OSAS and the timing of surgery with the permanency of cardiovascular disturbances is discussed.